Strengthening legal certainty in the construction sector through the reconstruction of criminal sanctions for building failures - Nasirin, Khoirun; Zaini, Naya Amin; Suryandari, Wieke Dewi (Indonesian Journal of Multidisciplinary Science, 2024)
The construction sector is vital for Indonesia's national economic development and infrastructure growth, serving as a foundation for public welfare and the built environment. However, the legal framework governing this sector faces significant challenges, particularly in addressing building failures and their associated accountability. The absence of clear definitions and specific criminal sanctions in Law No. 2 of 2017 on Construction Services creates legal uncertainty, undermining both accountability and enforcement mechanisms. This study analyzes regulatory gaps, focusing on weaknesses in existing legal provisions related to construction failures and exploring avenues for reconstructing criminal sanctions to enhance legal certainty and justice. Utilizing a normative juridical research method, the study identifies the ambiguity in defining construction failures and the lack of proportional sanctions as critical barriers to ensuring compliance, safety, and quality standards in the industry. The findings highlight the necessity for legislative reforms to provide a comprehensive definition of construction failure, establish proportional criminal sanctions, and implement effective dispute resolution mechanisms. Such measures aim to strengthen legal protections, foster industry accountability, and promote safer and higher-quality construction practices, contributing to the advancement of Indonesia’s construction sector and public interest.